2022
DOI: 10.1021/acs.jafc.2c01773
|View full text |Cite
|
Sign up to set email alerts
|

Safranal Treatment Induces Sirt1 Expression and Inhibits Endoplasmic Reticulum Stress in Mouse Chondrocytes and Alleviates Osteoarthritis Progression in a Mouse Model

Abstract: Osteoarthritis (OA) is an age-related degenerative disease. Oxidative stress (OS) modulates OA pathogenesis by enhancing chondrocyte apoptosis and extracellular matrix (ECM) degeneration via activation of the endoplasmic reticulum (ER) stress. Prior studies revealed that safranal plays a critical role in multiple diseases treatments, but there are no reports on its effect on OA. Therefore, investigating the effect of safranal on OA is needed. As a compound that can lead excessive reactive oxygen species (ROS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
10
1
Order By: Relevance
“…And ow cytometry revealed inhibition of chondrocyte apoptosis. Moreover, studies have reported that decreased SIRT1 expression leads to increased ROS levels in chondrocytes 35 , whereas our experimental results revealed that CAR reduced ROS levels in chondrocytes, which may be related to the activation of SIRT1 by CAR. Thus, CAR protects chondrocytes against iron overload-induced apoptosis via the SIRT1 signaling pathway.…”
Section: Discussioncontrasting
confidence: 58%
“…And ow cytometry revealed inhibition of chondrocyte apoptosis. Moreover, studies have reported that decreased SIRT1 expression leads to increased ROS levels in chondrocytes 35 , whereas our experimental results revealed that CAR reduced ROS levels in chondrocytes, which may be related to the activation of SIRT1 by CAR. Thus, CAR protects chondrocytes against iron overload-induced apoptosis via the SIRT1 signaling pathway.…”
Section: Discussioncontrasting
confidence: 58%
“…These three receptors are inactive under physiological conditions by binding to glucose regulated protein 78/immunoglobulin binding protein (GRP78/BiP) ( Huang et al, 2022 ). When endoplasmic reticulum stress is stimulated, GRP78 is activated and dissociates, and PERK catalyzes eukaryotic translation initiation factor 2α (eIF2-α) phosphorylation, increases CCAAT/enhancer-binding protein homologous protein (CHOP) expression, and activates the TXNIP-NLRP3 inflammatory vesicle complex, which ultimately leads to inflammation and fibrosis ( Ayaub et al, 2016 ; Wu et al, 2018 ; Zhang et al, 2022b ; Dong et al, 2022 ). In our study, we proved that CHR inhibited the expression of GRP78, ATF-6, TXNIP and the overproduction of PERK, IRE1α, CHOP, TXNIP and NLRP3 at the protein and mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue loss under normal physiological conditions can be compensated by the new matrix molecules synthesized by the chondrocytes . However, the high levels of matrix loss, previously thought to be a result of OA, that exceed the ability of chondrocytes to synthesize the matrix result in misfolded protein accumulation . Misfolded proteins can be recognized by specific stress sensors, and the unfolded protein response is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, the high levels of matrix loss, previously thought to be a result of OA, that exceed the ability of chondrocytes to synthesize the matrix result in misfolded protein accumulation. 34 Misfolded proteins can be recognized by specific stress sensors, and the unfolded protein response is initiated. The molecular chaperone BiP, which binds to ATF6, PERK, and IRE1 in the endoplasmic reticulum membrane, dislocates from these molecules and binds to misfolded proteins.…”
Section: Effect Of Ck and Tm On Ersmentioning
confidence: 99%